Roughness study on homogeneous layer panels manufactured from treated wood waste - Nascimento, Maria Fátima do; Christoforo, André Luis; Fiorelli, Juliano; Varanda, Luciano Donizeti; Macedo, Laurenn Borges de; Lahr, Francisco Antonio Rocco (Acta Scientiarum. Technology, 2017)
Natural resource exploration is growing, highlighting woods and joinery waste, wood industries and the like. This study presents homogeneous particleboard (PPH) roughness characterization manufactured from treated wood waste. Normative document with values of Brazilian Technical Standard Association ABNT NBR 8404 (1984), was adopted as a reference. The results show that the manufactured PPH showed roughness class N 10, with roughness values (Ra) of less than 12.5 microns. Â 